Strategic Deconfliction of 4D Trajectory and Perturbation Analysis for Air Traffic Control and Automation System - Xinmin Tang; Yu Zhang; Ping Chen; Bo Li; Songchen Han (Discrete Dynamics in Nature and Society)
Strategic 4D trajectory conflict-free planning is recognized as one of the core technologies of next-generation air traffic control and automation systems. To resolve potential conflicts during strategic 4D conflict-free trajectory planning, a protection-zone conflict-control model based on air traffic control separation constraints was proposed, in which relationships between expected arrival time and adjusted arrival time at conflicting waypoints for aircraft queues were built and transformed into dynamic linear equations under the definition of max-plus algebra. A method for strategic deconfliction of 4D trajectory was then proposed using two strategies: arrival time adjustment and departure time adjustment. In addition, departure time and flight duration perturbations were introduced to analyze the sensitivity of the planned strategic conflict-free 4D trajectories, and a robustness index for the conflict-free 4D trajectories was calculated. Finally, the proposed method was tested for the Shanghai air traffic control terminal area. The outcomes demonstrated that the planned strategic conflict-free 4D trajectories could avoid potential conflicts, and the slack time could be used to indicate their robustness. Complexity analysis demonstrated that deconfliction using max-plus algebra is more suitable for deconfliction of 4D trajectory with random sampling period in fix air route.